Phylogeography of Blue Corals (Genus Heliopora) Across the Indo-West Pacific - Taninaka, Hiroki; Maggioni, Davide; Seveso, Davide; Huang, Danwei; Townsend, Abram; Richards, Zoe T.; Tang, Sen-Lin; Wada, Naohisa; Kikuchi, Taisei; Yuasa, Hideaki; Kanai, Megumi; De Palmas, Stéphane; et al. (Frontiers in Marine Science, 2021)
Species delimitation of corals is one of the most challenging issues in coral reef ecology and conservation. Morphology can obscure evolutionary relationships, and molecular datasets are consistently revealing greater within species diversity than currently understood. Most phylogenetic studies however have examined narrow geographic areas and phylogeographic expansion is required to obtain more robust interpretations of within- and between- species relationships. In the case of the blue coral Heliopora, there are currently two valid species (H. coerulea and H. hiberniana) as evidenced by integrated genetic and morphological analyses in northwestern Australia. There are also two distinct genetic lineages of H. coerulea in the Kuroshio Current region which are morphologically and reproductively different from each other. Sampling from of all Heliopora spp. across the Indo-Pacific is essential to obtain a more complete picture of phylogeographic patterns. To examine phylogenetic relationships within the genus Heliopora, we applied Multiplexed ISSR Genotyping by sequencing (MIG-seq) method for >1,000 colonies across the Indo-West Pacific. Maximum likelihood phylogenetic trees indicated the examined Heliopora samples comprise three genetically distinct groups: H. coerulea group, H. hiberniana group, and a new undescribed Heliopora sp. group with further subdivisions within each group. Geographic structuring is evident among the three species with H. hiberniana group found in the Indo-Malay Archipelago and biased toward the Indian Ocean whilst Heliopora sp. was only found in the Kuroshio Current region and Singapore, indicating that this taxon is distributed in the western Pacific and the Indo-Malay Archipelago. Heliopora coerulea has a wider distribution, being across the Indian Ocean and western Pacific. This study highlights the effectiveness of phylogenetic analysis using genome-wide markers and the importance of examining populations across their distribution range to understand localized genetic structure and speciation patterns of corals.